The course of the spatial extent of pain in nonspecific chronic back pain: a prospective population-based cohort ctudy with clinical evaluation - Tesarz, Jonas; Gerhardt, Andreas; Hartmann, Mechthild; Kohlmann, Thomas; Eich, Wolfgang (The clinical journal of pain, 2016)
Objectives: - Longitudinal population-based studies on the natural course of nonspecific chronic back pain (nsCBP) concerning the spatial extent of pain are scarce. This study aims to assess the natural course of nsCBP patients concerning their spatial extent of pain and physical impairment over time. - Methods: - Analyses were based on a prospective, population-based survey with clinical evaluation. A representative population-based sample of 4000 German adults was sent a pain questionnaire. Patients mentioning nsCBP in the questionnaire were invited to a comprehensive clinical evaluation, including 1- and 2-year follow-ups. On the basis of pain drawings, the course of the spatial extent of pain over time was classified as “constant-local,” “constant-widespread,” “constant-amelioration,” “constant-spreading,” or “variable.” Physical impairment was assessed by the Back Performance Scale as an objective clinical assessment tool that measures self-reported activity limitation in daily functioning caused by nsCBP. - Results: - Pain drawings and physical assessment from 3 visits were available from 165 patients. The course of the spatial extent of pain was constant-local in 39.4% and constant-widespread in 18.2% of all patients, whereas 11.5% reported a variable course. Constant-amelioration was observed in 18.2% and constant-spreading was observed in 12.7%. Physical impairment remained unchanged over the time in all groups and was worst in the constant-widespread group. - Discussion: - Most nsCBP patients report a stable pain extent over the time of the study, whereas a constant spread of pain is observed only in a minority of nsCBP patients. These findings challenge the concept of a continuous transition from local to widespread pain.